The estimation the size of erosion in the Merka Sur valley In Erbil - M. Hussein Kadhim Abdul-Hussein; Assist. prof. Dr. Ahmed Abdel Sattar al-Athari (الأستاذ, 2018)
The study aims to study the estimation the size of erosion in the Merka Sur valley , that located in Erbil in northern of Iraq as part of simple torsion mountain region (1000 - 2100) m , with a basin area (162.1 km2).